Mechanism of negative cooperativity in glyceraldehyde-3-phosphate dehydrogenase deduced from ligand competition experiments. - Henis, Y I (1980)
It is shown that the modulation in the negative cooperativity of ligand binding by another, competing ligand that binds noncooperatively is accounted for exclusively by the ligand-induced sequential model. It is therefore suggested that whenever such a phenomenon is observed it argues strongly in favor of the sequential model. The advantages and limitations of this approach are evaluated. The binding of the coenzymes NAD+ and nicotinamide-1-N6-ethenoadenine dinucleotide to rabbit muscle apo-glyceraldehyde-3-phosphate dehydrogenase [D-glyceraldehyde-3-phosphate:NAD+ oxidoreductase (phosphorylating; EC 1.2.1.12] exhibits strong negative cooperativity, whereas acetylpyridine adenine dinucleotide, ATP, and ADP-ribose bind noncooperatively to the NAD+ sites. The strong abolished in the presence of acetylpyridine adenine dinucleotide and strongly weakened by ATP, ADP, and AMP, but was not affected by addition of ADP-ribose. These findings demonstrate that the negative cooperativity in coenzyme binding to this enzyme results from sequential conformational changes and exclude the pre-existent asymmetry model as a possible explanation. These results also support the view that the structure of the pyridine moiety of the coenzyme analogs plays a role in orienting the adenine moiety at the adenine subsite, therefore affecting the cooperativity in the binding of the coenzyme analog which is mediated through the adenine subsites.